Holographic reconstruction of Pt(110) using multiple wave number photoelectron diffraction patterns - Steinrück, Hans-Peter; et al. (Surface Science, 1994)
Angular distributions of Pt4f 7 2 and 4f 5 2 photoelectrons were measured for the reconstructed Pt(110)l × 2 surface at six different kinetic energies ranging from 120 up to 370 eV, using an angle-multichannel electron analyzer. From the photoelectron diffraction patterns, holographic reconstructions were performed using (1) the single wave number reconstruction method and (2) the multiple wave number phased sum method. The results obtained from the two photoemission lines are overall very similar. For the single energy reconstruction, the quality of the reconstructed images strongly depends on the kinetic energy of the photoelectrons: at high kinetic energies (370 eV) the reconstructed images are dominated by the maxima attributed to the nearest neighbors in the plane above the emitter; at low kinetic energies (120 eV) artifacts dominate. The multiple wave number algorithm leads to strong twin-image suppression, a reduction of certain artifacts but no noticeable improvement of resolution. While the overall quality of the reconstructed images increases when using the multiple energy algorithm, the best quality is observed for the single energy reconstruction for a kinetic energy of 370 eV. In all cases the atomic positions are shifted from their true values by 0.2-0.3 Å due to the phase shift in the scattering process. © 1994.